(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In this article are considered the features of a lyrical plot of Kazakh poet O. Suleymenov. The main attention is paid to nonlinearity of structure of his plot. Such plot generates possibility of new «reading» of the text. Object of interpretation is a visual Suleymenov’s plot. Visuality was a distinctive feature of poetry of men of the sixties, in particular, of Andrey Voznesensky. The interpretation of a plot of one of «picturesque» verses of Olzhas Suleymenov offered by authors reveals functions of reminiscences. It allows the poet to conduct invisible dialogue with Levitan. Interpretation gives the chance to understand sense of reception of an ekfrasis as attempts to retell the matter of work of painting by methods of lyrics. Authors of article investigated features of a visual code of lyrics of Suleymenov to find analogies and associations with Levitan’s pictures.